TRANSMITTING RELIGIOUS MODERATION: THE ROLE OF KITAB KUNING IN THE CULTURAL REPRODUCTION AT PESANTREN NURUT TAQWA - Dodik Harnadi; Suheri Suheri (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2026)
Kitab kuning (the Yellow Book) constitutes a central element of Islamic boarding school (pesantren) intellectualism in Indonesia. The religious understanding cultivated within these institutions is primarily derived from this classical literature. The kitab kuning’s heterogeneous content, combined with ongoing scholarly dialogue and debate among traditional scholars, ensures a dynamic and non-monolithic interpretation of Islam. In promoting moderate religious understanding (wasathiyyah), the kitab kuning functions as the primary form of cultural capital within pesantren. This study examines how pesantren fulfill the role of cultural reproduction, particularly regarding the transmission of moderate Islamic values, through the teaching of the kitab kuning. Employing a qualitative methodology, the research integrates a comprehensive literature review with empirical field data collected at the Nurul Taqwa Islamic Boarding School in Bondowoso, East Java. Drawing on Pierre Bourdieu's concept of cultural reproduction, the findings indicate that the pedagogical tradition of the kitab kuning serves as a significant resource for reinforcing and transmitting values of moderation to students (santri). This reproduction process is facilitated not only by traditional teaching methods, such as bandongan and sorogan, but is also fundamentally supported by the authoritative scholarly capacity and habitus of the teaching figures (kyai and asatidz). Their demonstrated expertise in classical texts plays a crucial role in shaping a tolerant and inclusive religious perspective.